(untitled) (Academicia Globe: Inderscience Research, 2023)
The article discusses the use of cloud technologies in the field of education, examples of the use of cloud technologies in education are given. The importance of the introduction and use of cloud technologies in education of the Republic of Uzbekistan is analyzed. It was revealed that cloud technologies in education allow using a wider range of forms and methods of teaching, and are one of the modern ways of intensifying and optimizing the educational process.